Pedestal and Er profile evolution during an edge localized mode cycle at ASDEX Upgrade. (17th August 2017) - Cavedon, M; Pütterich, T; Viezzer, E; Laggner, F M; Burckhart, A; Dunne, M; Fischer, R; Lebschy, A; Mink, F; Stroth, U; Willensdorfer, M; Wolfrum, E
Abstract: The upgrade of the edge charge exchange recombination spectroscopy diagnostic at ASDEX Upgrade has enabled highly spatially resolved measurements of the impurity ion dynamics during an edge-localized mode cycle (ELM) with unprecedented temporal resolution, i.e. 65 μ s. The increase of transport during an ELM induces a relaxation of the ion, electron edge gradients in impurity density and flows. Detailed characterization of the recovery of the edge temperature gradients reveals a difference in the ion and electron channel: the maximum ion temperature gradient ∇ T i is re-established on similar timescales as ∇ n e, which is faster than the recovery of ∇ T e . After the clamping of the maximum gradient, T i and T e at the pedestal top continue to rise up to the next ELM while n e stays constant which means that the temperature pedestal and the resulting pedestal pressure widen until the next ELM. The edge radial electric field E r at the ELM crash is found to reduce to typical L-mode values and its maximum recovers to its pre-ELM conditions on a similar time scale as for n e and T i . Within the uncertainties, the measurements of E r align with their neoclassical predictions E r, neo for most of the ELM cycle, thus indicating that E r is dominated by collisional processes. However, between 2 and 4 ms after the ELM crash, other contributions to E × B flow, e.g. zonal flows or ion orbit effects, could not be excluded within the uncertainties.